Peran Generasi Muda sebagai Fasilitator dalam Penggunaan Dompet Digital (Reinforce: Journal of Sharia Management, 2024)
The rapid technological advancements in the globalization era have significantly influenced various aspects of human life, including economic transactions. The adoption of digital wallets has transformed traditional cash-based transactions into more efficient and secure digital payment methods. This study explores the role of youth as facilitators in promoting the use of digital wallets, which are increasingly integral to Indonesia's digital economy. Youth, as active users and contributors to technological advancements, play a vital role in educating and guiding older generations in the adoption of these tools. The study uses a literature review approach to analyze the impact of digital wallets on Indonesia's economic landscape. Findings highlight that digital wallets offer numerous benefits, such as transaction efficiency, enhanced security, and ease of financial management. Factors driving the shift to digital payments include globalization, technological advancements, and external events like the COVID-19 pandemic, which accelerated digital adoption. Digital wallets contribute to reducing cash circulation, controlling inflation, and fostering economic resilience through cost-effective financial operations and support for small businesses via QRIS integration. Youth act as enablers of this transition by leveraging their technological fluency to facilitate older generations’ adaptation to digital tools. Furthermore, the involvement of youth in entrepreneurial activities utilizing digital platforms strengthens economic growth and positions Indonesia competitively in the global digital economy. This study underscores the importance of intergenerational collaboration and the strategic role of youth in accelerating digital transformation and fostering sustainable economic development in Indonesia.
Keywords: digital wallets; youth role; digital economy; economic growth; technological adoption; dompet digital; generasi muda; teknologi keuangan; ekonomi digital; transformasi digital